The Analysis of Economic Integration Among Asean-5 With Japan and USA - Manaka, Ganeisan (Universiti Malaysia Sarawak, (UNIMAS), 2008)
This study examines the existence of economic integration among the five founding member countries of the Association of Southeast Asian Nations (ASEAN) which is Indonesia, Malaysia, the Philippines, Thailand and Singapore. Further, this study also explores the economic integration among ASEAN-5 with Japan and USA by using the real GDP data from 1970-2005. Basically there are three types of test applied consists of Unit Root Test, Johansen and Juselius Cointegration Test And Granger Causality Test. The unit root test implies that all the data are stationary at their first differences. This allowed proceeding with cointegrating test. By using lag 2 and 4, there are long-run relationship occurs among ASEAN-5 countries itself and ASEAN-5 with Japan and USA respectively. Whereas, the granger causality test shows there is short-run relationship occurs among ASEAN-5 with Japan and USA. The analysis of this study shows that the ASEAN -5 has economic integration among the region itself. In addition, the study also found that Japan significantly affects the changes ofoutput of ASEAN-5 rather than USA.